Gold Nanoparticle@Polyhedral Oligomeric Silsesquioxane Hybrid Scaffolds in Microfluidic Format – Highly Efficient and Green Catalytic Platforms. Issue 7 (4th February 2016) - Scholder, Pascal; Hafner, Martina; Hassel, Achim W.; Nischang, Ivo
Abstract: We report on the preparation of new hybrid organic–inorganic multiporous monolithic capillary columns carrying gold nanoparticles of 5, 10, 50, and 100 nm size and their use as flow‐through catalytic platforms for aqueous liquid‐phase reduction reactions. We found that the flow‐through performance of the reactors depends not only on the size of the gold nanoparticles but also on the interplay of the pore size of the scaffolds and the catalytically available gold surface within the system, that is, loading an increased number of gold nanoparticles of smaller size does not necessarily result in strictly improved performance. This indicates the importance of the interplay between the nanopore size of the scaffolds and the catalytically active gold surface existing within the system. Demonstration of the highly efficient catalytic flow‐through operation within seconds and the repeated use of the reactors without loss of performance indicates their excellent suitability as microfluidic device elements. Abstract : Hybrid organic–inorganic porous monolithic materials were prepared in situ in small conduits. Their internal structure is decorated with gold nanoparticles anchored by pendant thiol groups through thiol–gold interactions. The materials are efficient catalysts, and their repeated use under continuous flow catalysis conditions results in no loss of performance, which indicates their robustness.